Six easy pieces essentials of physics, explained by its most brilliant teacher - Feynman, Richard P (Richard Phillips) 1918-1988; Leighton, Robert B.; Sands, Matthew L. (Matthew Linzee); Rogers D. Spotswood Collection (Cambridge, Massachusetts Perseus Books, 1995)
Presents six of the easiest chapters from the Nobel Prize winner's celebrated text Lectures in Physics, originally published in 1963, which comprised the lectures he prepared for undergraduate students at Caltech in the early 1960s. Addressing key topics in largely qualitative terms without formal mathematics, the six selections discuss atoms in motion, basic physics, the relation of physics to other sciences, conservation of energy, the theory of gravitation, and quantum behavior.
Atoms in motion -- Basic physics -- The relation of physics to other sciences -- Conservation of energy -- The theory of gravitation -- Quantum behavior.
Includes index.
Keywords: Physics